Sarcopenia defined with L3-SMI is an independent predictor of survival in male patients with ARLD in mainland China - Zhang, Yu; Wei, Liangui; Chang, Chunyan; Duan, Fangfang; Quan, Min; Yang, Song (Frontiers in Nutrition, 2023)
The burden of alcohol-related liver disease (ARLD) is increasing in China. Patients with ARLD are more likely to have comorbid sarcopenia, which may impair their survival. This study aimed to evaluate the relationship between the prognoses of patients with ARLD and sarcopenia, identified using the skeletal muscle index at the third lumbar vertebra level (L3-SMI).Methods: Hospitalized patients with ARLD were retrospectively enrolled between 2015 and 2018 and followed up for 24 months to evaluate their survival profiles. Cox proportional hazards regression models were used to estimate patient survival factors. A receiver operating characteristic curve was created to identify the cut-off point of the L3-SMI for predicting the prognoses of Chinese patients with ARLD.The study enrolled 168 male patients with ARLD who were followed-up for 24 months or until a study endpoint was met. The overall L3-SMI in patients with ARLD was 42.61±9.15 cm 2 /m 2 , and 42.86% (72/168) of patients with ARLD were comorbid with sarcopenia. The overall survival in patients with ARLD was 77.38% at 24 months. The survival rate of patients with sarcopenia was lower than that of patients without sarcopenia (66.67% vs. 85.42%, P=0.004). Multiple Cox regression analysis showed that sarcopenia, abstinence, and baseline creatinine level were independent prognostic factors of 24-month survival with hazard ratios (95% confidence intervals) of 2.022 (1.025-3.991), 0.275 (0.122-0.617), and 1.018 (1.008-1.027), respectively. The cut-off value of the L3-SMI for predicting 24-month survival was 40.0 cm 2 /m 2 for male patients with ARLD. This is a provisional file, not the final typeset article Conclusion: Sarcopenia is an independent mortality risk factor in male patients with ARLD in mainland China. Early diagnosis and intervention of sarcopenia are important for optimizing the management of patients with ARLD.